INTELLECTUAL TRADITION AND OPENNESS THINK K.H. ABDURRAHMAN WAHID (STUDY OF K.H. ABDURRAHMAN WAHID THOUGHT FIGURES) - Fatkhur Rohman (UNIVERSITAS PAKUAN, 2022)
This paper seeks information about K.H. Abdurrrahman Wahid, also known as Gus Dur, and his intellectual tradition and open-mindedness. This article was written using qualitative research methods and a character study approach of the library research type. According to the author's research into the literature, there are several intellectual traditions and Gus Dur's open-mindedness, namely: First, Gus Dur's intellectual traditions are depicted through scientific works that are recorded, published, and made available to the public, and are based on the thoughts of Muslims in general, and particularly in organizations. Nahdlatul Ulama is Indonesia's largest. Second, Gus Dur's openness to new ideas is reflected in his interactions with interfaith, social, political, and educational leaders of all backgrounds. This resulted in polarization in Gus Dur's mind, which was sometimes inaccessible by ordinary reason and necessitated deep interpretation.Â